Theoretical analysis of the explosion limits of hydrogen-oxygen mixtures and their stability. (31st December 2018) - Lidor, A.; Weihs, D.; Sher, E.
Highlights: We study the explosion limits of the H2 -O2 system. We propose a unique concept for explaining the branching behavior, based on thermodynamic stability analysis. We demonstrate this approach on the upper and intermediate limits of the explosion limits of the H2 -O2 system. We show that the reactants and products exhibit opposite behavior in terms of their stability. Abstract: We present here a novel explanation for the explosion limits phenomenon, based on the concept of thermodynamic stability analysis of the fuel-oxidizer mixture. This concept is demonstrated by a detailed statistical thermodynamic analysis of the explosion limits of the H2 –O2 system. It is shown that while the magnitude of the relative fluctuations in the number of molecules is very small, the reactants approach their thermodynamic stability limit at the explosion limit, thus contributing to the onset of self-ignition. It is also found out that the products (H2 O) behave in an opposite manner, being on the verge of stability in the non-explosive region, and becoming stable above the explosion limit. The different chain-carriers are on the verge of thermodynamic stability over the complete range (both explosive and non-explosive regions), a fact that sits well with their short residence time as known from chemical kinetics and experiments. We conclude that the unique nature of the branching limits phenomenon can be considered as a thermodynamic stability problem, promoting the idea that a universal self-ignition criterion can be developed.